Doliocarpus stehmannii (Doliocarpoideae, Dilleniaceae): a new species of water vine from Brazil - Monzoli, João Victor Longhi; Aymard, Gerardo; Araújo, Michelly De Deus Felipe; Fraga, Claudio Nicoletti De; Sampaio, Daniela (Phytotaxa, 2025)
A new species of Doliocarpus (Dilleniaceae) collected in the Brazilian Atlantic Forest (southern center of the state of Minas Gerais) is presented. Doliocarpus stehmannii is morphologically similar to Doliocarpus hispidus, but the latter occurs in northwestern Colombia and Central America. The new species can be distinguished by the lack of brachyblasts (vs. presence of brachyblasts in D. hispidus), 8−11 pairs of secondary veins (vs. 15−20), adaxial surface of the sepals glabrous (vs. pubescent) and glabrous fruits (vs.pubescent). Finally, we provide the first identification key for the 42 species of Doliocarpus from Brazil.